Geomorphic and hydrologic controls of dust emissions during drought from Yellow Lake playa, West Texas, USA. (October 2016) - Sweeney, M.R.; Zlotnik, V.A.; Joeckel, R.M.; Stout, J.E.
Abstract: Numerous complex geomorphic and hydrologic factors have been identified that control dust emissions from playas, yet there are few measurements of dust emissions from playas during drought, which is assumed to enhance emissions, or during low-emission seasons. We used the PI-SWERL (Portable in situ Wind Erosion Laboratory) to measure dust emission potential at Yellow Lake, a saline playa in West Texas, USA, during the drought of 2011. Direct aeolian entrainment of dust occurred primarily on supply-limited surfaces consisting of mud-cracked surfaces as well as crusts containing halite, thenardite, and gypsum. High-magnitude, low duration peaks in dust emissions occurred over parts of the playa underlain by shallow groundwater (<1 m) where conditions encouraged the crystallization of efflorescent salts. In contrast, surfaces characterized by loose sand-sized aggregates produced sustained dust emissions two to three orders of magnitude higher than the playa surface because aggregates broke apart during saltation. Prolonged drought at Yellow Lake will significantly change the frequency and type of dust emissions. We propose that a similar scenario characterizes dust production at many hydrologically similar playas. More research is needed to assess the impacts of changing groundwater levels on dust emissions in the context of extended drought and anthropogenic climate change. Highlights: Saline playas produce limited dust via direct entrainment during drought. Efflorescent salts produce dust, influenced by water table depth. Saltating mud aggregates produce 2–3 orders of magnitude more dust than the playa.